Development of a live coding method to assess infant/toddler food acceptance. Issue 3 (26th May 2022) - Moding, Kameron J.; Bonvecchio Arenas, Anabelle; Rawlinson, Cloe; Okronipa, Harriet; Pacheco‐Miranda, Selene; Boenig, Rebecca; Flesher, Abigail E.; Johnson, Susan L.
Abstract: Validated measures predicting infant consumption of nutrient supplements or fortified foods are essential for the success of nutritional interventions to improve undernutrition. Behavioural coding of food acceptance is one promising approach, though the required time and resources are limiting. The overarching goal of the present study was to adapt a video coding (VC) protocol for use as a live coding (LC) method to assess infant food acceptance in naturalistic settings. Infants ( n  = 59; ages 7–24 months) were fed a small‐quantity lipid‐based nutrient supplement (SQ‐LNS) mixed with a familiar food by caregivers in the State of Morelos, Mexico. Trained coders used a VC scheme to rate infant acceptance of each spoon offer using a 4‐point scale. The VC scheme was subsequently adapted for use as an LC method to be used in participant homes and a video live coding (VLC) method to monitor reliability. Reliability and validity of the LC method were tested in a subsample of dyads ( n  = 20). Intraclass correlation coefficients (ICCs) indicated that the inter‐rater reliability between coders using the LC method was moderate or good when compared to VC methods (ICCs = 0.75 and 0.87). Live coded acceptance scores were also moderately associated with consumption of the SQ‐LNS ( ρ  = 0.50, p  = 0.03). The LC scheme demonstrated initial reliability and validity as an assessment of infant food acceptance. Since VC is both resource and time‐intensive, the LC scheme may be useful for assessing infant food acceptance in resource‐limited settings. Abstract : The overarching goal of the present study was to adapt a video coding protocol for use as a live coding method to assess infant food acceptance in naturalistic settings. The results of this study suggest initial reliability and validity of this coding scheme. Key messages: Current measures to assess infant food acceptance in nutritional interventions are limited. This study presents a live coding scheme and protocol that can be used to objectively rate infants' food acceptance in naturalistic settings. The coding method demonstrated initial reliability with video coding methods and was associated with infants' consumption of a target food. The live coding protocol may be particularly useful for assessing infant food acceptance in resource‐limited settings.